2015
DOI: 10.1183/13993003.02345-2014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of rhinitis and asthma related to welding in Northern Europe

Abstract: Welding-related asthma is well recognised but less is known about rhinitis in relation to welding. The aim here, was to study associations between welding, rhinitis and asthma in a general population sample, and factors influencing selection into and out of a welding occupation.Adult-onset asthma and non-infectious rhinitis were investigated in the international multicentre population-based Respiratory Health in Northern Europe (RHINE) study, including 16 191 responders aged 26-54 years. Ever welding (n=2181),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Our findings were supported by several studies (2,3,18). Our results revealed that respiratory symptoms amongst the welders' group were much more than in the non-welders group and phlegm, wheezing and cough symptoms were more common symptoms (5,6,23). In other studies by El-Zein et al, dry cough, shortness of breath, metallic taste and wheezing were common complaints among welders during the first days of the working week (3).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings were supported by several studies (2,3,18). Our results revealed that respiratory symptoms amongst the welders' group were much more than in the non-welders group and phlegm, wheezing and cough symptoms were more common symptoms (5,6,23). In other studies by El-Zein et al, dry cough, shortness of breath, metallic taste and wheezing were common complaints among welders during the first days of the working week (3).…”
Section: Discussionsupporting
confidence: 80%
“…Work-related respiratory diseases have been well documented for welders in many studies (1)(2)(3)(4)(5)(6)(7). Air pollutants released from welding activities are capable of initiating several acute and chronic respiratory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unsatisfactory leisure time was associated with decreased reported medical treatment or consultation for disorders of the shoulder (PR = 0.7, 95% CI 0.3–1.7). The REBUS Study High-Income ( Fredriksson et al, 1999 ) Longitudinal Duration of exposure, age, smoking, BMI, living alone with children, job strain, social support, stress Shoulder Disorders Exposure-outcome among blue-collar women Among female sewing machine operators, the risk of developing a shoulder disorder for those wit high versus low shoulder support (RR = 3.72, 95% CI 1.22–11.30), increased neck-shoulder pain scores (RR = 1.02, 95% CI 1.00–1.05), smoking (RR = 3.93, 95% CI 1.33–11.58), and living alone with children (RR 3.58, 95% CI 0.87–14.68). Danish Project on Research and Intervention in Monotonous Work (PRIM Study) High-Income ( Kaergaard and Andersen, 2000 ) Longitudinal Job demand, job control, supervisor support, coworker support, age, work duration Work injury Exposure-outcome among blue-collar women The odds of work injury among blue-collar were increased among those with high job demand (OR = 1.30, SE = 0.08331).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies assessed risk factors for musculoskeletal disorders among blue-collar women. Specific risk factors identified included psychological or physical strain ( Stokholm et al, 2013 , Storaas et al, 2015 , Strong and Zimmerman, 2005 , Taiwo et al, 2008 , Takao et al, 2003 , Takezaki et al, 2001 , Tessier-Sherman et al, 2014 ) uncomfortable or inadequate work arrangements ( Stokholm et al, 2013 , Strong and Zimmerman, 2005 , Thilsing et al, 2012 , Thompson et al, 2005 ); age ( Tsai et al, 1997 , Takao et al, 2003 , Takezaki et al, 2001 ); tenure ( Strong and Zimmerman, 2005 , Tsai et al, 1997 , Takao et al, 2003 ); household arrangement ( Stokholm et al, 2013 , Thilsing et al, 2012 ); and sitting time ( Hallman, Gupta, Mathiassen, & Holtermann, 2015 ). The majority of these studies were conducted either in Scandinavian countries (e.g.…”
Section: Description Of Findings By Health Outcome Categorymentioning
confidence: 99%
“…However, it remains difficult to distinguish occupational asthma from work exacerbated asthma symptoms or occupational COPD among smelters 39,41 . In a recent longitudinal study in Northern Europe (RHINE), incidence of asthma and rhinitis were associated with welding 42 .…”
Section: Other Work Environments With High Likelihood Of Irritant Expmentioning
confidence: 99%